2020
DOI: 10.1021/acsnano.9b08638
|View full text |Cite
|
Sign up to set email alerts
|

Laser Writing of Janus Graphene/Kevlar Textile for Intelligent Protective Clothing

Abstract: Protective clothing plays a vital role in safety and security. Traditional protective clothing can protect the human body from physical injury. It is highly desirable to integrate modern wearable electronics into a traditional protection suit to endow it with versatile smart functions. However, it is still challenging to integrate electronics into clothing through a practical approach while keeping the intrinsic flexibility and breathability of textiles. In this work, we realized the direct writing of laser-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
181
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(183 citation statements)
references
References 47 publications
1
181
0
1
Order By: Relevance
“…Patterned graphene has been proved to be an excellent deformation sensitive material for flexible strain sensors in previous studies. [ 37–41 ] However, few studies focus on the substrate/graphene interface modification to optimize the basic performance of sensors. Our graphene patterning technique also represents an effective interface enhancement method and meets the sensor requirement of high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Patterned graphene has been proved to be an excellent deformation sensitive material for flexible strain sensors in previous studies. [ 37–41 ] However, few studies focus on the substrate/graphene interface modification to optimize the basic performance of sensors. Our graphene patterning technique also represents an effective interface enhancement method and meets the sensor requirement of high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of elastomer (as matrix to form composite or function as substrate) and structural design can improve stretchability of on‐skin electrodes, while metallic nanomaterials based composites usually demonstrate high conductivity due to superior high conductivity of metals. For instance, stretchable polymer substrate such as silicone‐based substrates, [ 56,200 ] textile‐based substrates, [ 201 ] and protein‐based substrates [ 202 ] had been investigated and elastic composites such as PDMS−ECCs, [ 102 ] AgNWs–PDMS mixtures, [ 103 ] and Ag‐PU nanocomposites [ 101 ] had been synthesized. Regarding structural design, typical deformable structures such as filamentary serpentine, [ 203 ] wrinkles, [ 60 ] and kirigami [ 204 ] have been implemented.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Sensors can be embedded in a number of mobile devices so that they are widely used, and a lot of corresponding reports have been released For Instance, Wang et al had reported a graphene/Kevlar textile for wearable sensor. [67] They have integrated modern wearable electronics into protective suits, allowing them to perform more functions, and they directedly wrote the laser-induced www.advancedsciencenews.com www.biotechnology-journal.com CuO/PANI nanofiber Detect H 2 O 2 and glucose [17] Graphene/M 2+ Fluorescence sensors Detect metal ions [62] ZnONRs/TNs Detect AChE [49] Graphene/Kevlar textile Wearable sensors Detect NO 2 [67] BiVO 4 /2D-C 3 N 4 Detect DNA [48] RGO-PU sponge Pressure sensors - [46] SWNT/tissue paper [2] graphene (LIG) on a Kevlar textile. This as-synthesized material would be used as the intelligent protective clothing.…”
Section: Wearable Sensorsmentioning
confidence: 99%
“…had reported a graphene/Kevlar textile for wearable sensor. [ 67 ] They have integrated modern wearable electronics into protective suits, allowing them to perform more functions, and they directedly wrote the laser‐induced graphene (LIG) on a Kevlar textile. This as‐synthesized material would be used as the intelligent protective clothing.…”
Section: Flexible Biosensorsmentioning
confidence: 99%